HUBUNGAN PEMBERANTASAN SARANG NYAMUK (PSN) DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH PUSKESMAS KELURAHAN BELIAN KOTA BATAM - Aryaneta, Yenni; Yolanda, Sonia (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Dengue Hemorrhagic Fever is an acute viral infectious disease caused by a virus with the characteristics of a sudden high fever and a tendency to cause shock and death. This disease is transmitted through the bite of Aedes aegypti and possibly Albopictus mosquitoes. Environmental factors play a role in the occurrence of outbreaks. An environment where there is a lot of standing water and items that allow stagnant water are ideal places for the disease. The research objective is to increase the participation of families and communities in the prevention and control of DHF through the civilizing of PSN 3M Plus. This study using Case Control was conducted at the Belian Health Center Batam City in September 2019. The population and research sample, namely 80 residents, were found who did PSN well as many as 15 people (18.75%), and 25 people did not do PSN well ( 31.25%), 28 people (35.00%) in the group with no DHF incidence, and 12 people (15.00%). The sampling technique used by the author is that the sample is taken by purposive sampling. Processing The data obtained by using a check list, then with computer facilities, the data is processed through data processing as follows: Editing, Coding (Code Checking), Scoring (Assessment), Cleaning (Data Cleaning), Data Entry (Entering Data). The statistical results showed that there was a relationship between the eradication of mosquito nests and the incidence of dengue fever with p value = 0.04. The researcher concluded that there was a relationship between the eradication of mosquito nests (PSN) and the incidence of dengue hemorrhagic fever (DHF). Eradication in question is a preventive / handling measure to carry out cleanliness in the environment around housing or residential areas. Suggestions for respondents to better understand or pay attention to the cleanliness of their homes as often as possible to avoid mosquito attacks that are endemic.